Service Level Decision‐making in Rural Physiotherapy: Development of Conceptual Models. (21st April 2015) - Adams, Robyn; Jones, Anne; Lefmann, Sophie; Sheppard, Lorraine
Abstract: Background: Understanding decision‐making about health service provision is increasingly important in an environment of increasing demand and constrained resources. Multiple factors are likely to influence decisions about which services will be provided, yet workforce is the most noted factor in the rural physiotherapy literature. This paper draws together results obtained from exploration of service level decision‐making (SLDM) to propose 'conceptual' models of rural physiotherapy SLDM. Method: A prioritized qualitative approach enabled exploration of participant perspectives about rural physiotherapy decision‐making. Stakeholder perspectives were obtained through surveys and in‐depth interviews. Interviews were transcribed verbatim and reviewed by participants. Participant confidentiality was maintained by coding both participants and sites. A system theory‐case study heuristic provided a framework for exploration across sites within the investigation area: a large area of one Australian state with a mix of regional, rural and remote communities. Results: Thirty‐nine surveys were received from participants in 11 communities. Nineteen in‐depth interviews were conducted with physiotherapists and key decision‐makers. Results reveal the complexity of factors influencing rural physiotherapy service provision and the value of a systems approach when exploring decision‐making about rural physiotherapy service provision. Six key features were identified that formed the rural physiotherapy SLDM system: capacity and capability; contextual influences; layered decision‐making; access issues; value and beliefs; and tensions and conflict. Conclusions: Rural physiotherapy SLDM is not a one‐dimensional process but results from the complex interaction of clusters of systems issues. Decision‐making about physiotherapy service provision is influenced by both internal and external factors. Similarities in influencing factors and the iterative nature of decision‐making emerged, which enabled linking physiotherapy SLDM with clinical decision‐making and placing both within the broader healthcare context. The conceptual models provide a way of thinking about decisions informing rural physiotherapy service provision. Copyright © 2015 John Wiley & Sons, Ltd.